Examining the current situation of Individualized Curriculum Plan (ICP) Formulation in Maldivian Schools - Aishath Wadheefa; Adhila Rushdhee; Aishath Zaeema; Anula Saleem; Hussain, Haleemath; Abdul Sattar, Zuleykha (Jurnal Pendidikan Bitara UPSI, 2025)
This study highlights the current situation of schools in preparing Individual Curriculum Plans (ICP) for students with complex learning profiles (SCLP) in the Maldives, particularly after the redefinition of ICP in 2022. The transition from IEP (Individualised Education Plan) to ICP ensures that students’ learning is aligned with the curriculum objectives and competencies. While little is known about ICP development practise in the Maldives, this study provides insightful evidence on this issue enabling informed policy debates and recommendations on the current practises aimed at achieving inclusive education objectives. The study analyzed 2077 ICP documents from 213 schools and 622 of them were analysed in detail. It emphasizes the significant role ICPs play in supporting SCLP students, with over 80% of schools utilizing ICPs to offer support. However, several key issues in the ICP preparation process were identified, such as incomplete documentation, improper student placement in programs, and the lack of appropriate accommodations and assistive technology. The findings suggest that, while progress has been made in integrating ICPs into educational practices, there is still a need for further training, improved resources, and standardized guidelines to ensure the successful implementation of ICPs. By identifying the gaps in the current practices, this research offers the Department of Inclusive Education valuable insights to refine the ICP preparation process and improve educational support for students with complex learning profiles across the country.